ASUHAN KEBIDANAN IBU NIFAS DENGAN EFEKTIFITAS TEKNIK KOMPRES AIR HANGAT DAN AIR DINGIN TERHADAP BENDUNGAN ASI PADADI RUMAH IBU M KECAMATAN BUBON KABUPATEN ACEH BARAT - Tamita, Indah; Julianti, Rina; Yushida, Yushida; Zahara, Evi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The incidence of ASI dams caused by the release of milk that is not smooth, because the baby does not feed his mother often enough. An initial survey conducted in April 2025 at house mothers M , Bubon District, aceh barat, in 2025 found that there were 3 postpartum mothers who experienced ASI dams. To determine the effectiveness of giving warm and cold water compresses to breast milk dams in postpartum mothers. This study used a quasi-experimental with purposive sampling with a sample of 3 people. Data techniques included in uivariate analysis using frequency distribution and bivariate analysis using SPSS program statistical calculations. The results of this study indicate that the value of the Paired Sample Test obtained a sig (2-tailed) value of 0.000 <0.05, so there is a difference between the pretest and posttest values so that it can be concluded that there is an effectiveness of giving warm compresses and cold compresses to breast milk dams for Postpartum Mothers at house mothers M, Bubon District, aceh barat in 2025. There is an effectiveness of giving warm compresses and cold compresses to breast milk dams for Postpartum Mothers at house mothers M, Bubon District, aceh barat in 2025. It is hoped that the method of giving warm compresses and compresses cold as a reference for intervention against breast milk in postpartum mothers.